2016
DOI: 10.1016/j.apenergy.2016.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic optimization of a hybrid system of energy-storing cryogenic carbon capture and a baseline power generation unit

Abstract: Recently promulgated regulations of the US Environmental Protection Agency (EPA) aggressively limit CO 2 emissions from the US power industry. Carbon capture and increased utilization of renewable energy sources are viable approaches to reduce CO 2 emissions from the power industry. Cryogenic carbon capture considered in this study is a post-combustion CO 2 removal system that separates CO 2 from the flue gas by desublimation. In this investigation, a hybrid system of cryogenic carbon capture and a baseline fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Countries around the world have developed many technologies and proposed various policies to promote the development of renewable energy such as large-scale energy storage [1], feed-in tariffs (FIT) and renewable portfolio standards (RPS). Large-scale energy storage is a practical solution in adopting renewable energy resources in power grid as an important technology [2], and many countries have considered it as a viable solution to increase the contribution of renewable energy resources [3,4]. Renewable energy policies can also significantly contribute to the expansion of domestic industrial The model not only clearly shows the complex logical relationship between the factors but also reveals the process of coordination between the two policy tools in renewable energy power industry's development.…”
Section: Introductionmentioning
confidence: 99%
“…Countries around the world have developed many technologies and proposed various policies to promote the development of renewable energy such as large-scale energy storage [1], feed-in tariffs (FIT) and renewable portfolio standards (RPS). Large-scale energy storage is a practical solution in adopting renewable energy resources in power grid as an important technology [2], and many countries have considered it as a viable solution to increase the contribution of renewable energy resources [3,4]. Renewable energy policies can also significantly contribute to the expansion of domestic industrial The model not only clearly shows the complex logical relationship between the factors but also reveals the process of coordination between the two policy tools in renewable energy power industry's development.…”
Section: Introductionmentioning
confidence: 99%
“…Various CO 2 capture and sequestration technologies have been developed to reduce CO 2 emissions and the International Energy Agency (IEA) has announced that CO 2 capture and sequestration (CCS) technology will cover 19% of the total CO 2 reductions by 2050 [1][2][3][4][5][6]. Among them, geological sequestration will be deeply considered to reduce CO 2 emissions at low cost [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The MSFLA-LSSVM model is used to forecast the CO 2 The relative error of each prediction point is shown in Table 2. From Figure 3 and Table 2, it can be concluded that using the MSFLA-LSSVM model to forecast CO 2 emissions in China can obtain good forecasting results, and the forecasting curve has a good fitting degree with the actual curve.…”
Section: Forecasting Effect Test For Msfla-lssvm Modelmentioning
confidence: 99%
“…CO 2 is one of the main gases that cause the greenhouse effect. Carbon capture and storage is the process of capturing and storing the CO 2 in industrial production by various means, such as cryogenic carbon capture [1,2], chemical absorption [3], oxyfuel combustion [4] and so on. Carbon capture technologies that result in significant reduction in energy-related CO 2 emissions, specifically from coal-fired power plants, can relieve the greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation